Educational Praximorphisms: on the Irrational Nature of Educational Practice - Simone Digennaro (University of Bologna, 2020)
Nowadays, the debate concerning the crisis of the education, and afterthought of the educational approaches, is emerging as a reaction to the challenges of the modernity. The educational systems are not giving appropriated answers to the problems of the society that is different if compared with the past. Modern-day education is regarded to be open and based on a complex system that accepts the indeterminateness of the knowledge, by implementing the interventions on the basis of the given situation, as it goes along, without the dogmatism of a method defined a-priori.